A Grassmannian Su(5) X Su(5) Theory - Roleda, Robert C. (Animo Repository, 1995)
It has been shown that while anomaly-free grand unified models may be constructed by appending a complex Grassmannian internal manifold to the four-dimensional space-time, the models proposed are not asymptotically-free. Find.ing a new set of Grassmannian S U(5) generators, we proceed to develop an anomaly-free and asymptotically-free Grassmannian grand unified theory based on an SU(S) x SU(S) gauge group.